Potensi-Potensi Keunggulan Manusia Yang Bisa Dikembangkan Lewat Pendidikan - Nurhabibah Harahap; Nurbaya Harahap; Anisa Octavia; Indah Ayu Fitriani; Wismanto Wismanto (Lembag, 2024)
In essence, humans have potential, according to Islamic education, humans are equipped with basic potential in the form of physical (hearing, sight), reason, and spirit which still need development to prepare for life since birth. This development is influenced by the family, community and school environment. This development process will last a lifetime and aims to serve oneself to Allah SWT. So the basic potential is influenced by the environment (external factors). The aim of this research is to explain the potential for human excellence that can be developed through education. The approach in this research is a qualitative descriptive method, the type of research is library research, namely research through library or literary studies. The result of this research is the importance of developing the potential that humans have because humans are the noblest creatures among other creatures and they were made by Allah in the best form/event, both physically and psychologically, and are equipped with various potential tools. and basic potentials (fitrah) that can be developed and actualized as optimally as possible through the educational process.